Analysis of Buoyancy Driven Unsteady Nanofluid Channel Flow on Entropy Generation - Alex X. Matofali; Michael H Mkwizu (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study aimed investigates on the effects of buoyancy driven unsteady channel flow on entropy generation.The study intended to develop flow model for a case of nanofluid in a channel, determine the effect of different parameters on velocity, temperature and entropy generation. The obtained results reviled that Alumina-water nanofluid tends to raise the velocity than Copper-water nanofluid. Furthermore, the study indicated that the temperature is subjected to decrease with the increase in . Also the results show that the entropy generation rate decreases with an increase in nanoparticle fraction ( ), the vice versa results is observed when increasing an Eckert number (Ec).